2015
DOI: 10.1158/1535-7163.mct-14-0850
|View full text |Cite
|
Sign up to set email alerts
|

Identification of LY2510924, a Novel Cyclic Peptide CXCR4 Antagonist That Exhibits Antitumor Activities in Solid Tumor and Breast Cancer Metastatic Models

Abstract: Emerging evidence demonstrates that stromal cell-derived factor 1 (SDF-1) and CXCR4, a chemokine and chemokine receptor pair, play important roles in tumorigenesis. In this report, we describe a small cyclic peptide, LY2510924, which is a potent and selective CXCR4 antagonist currently in phase II clinical studies for cancer. LY2510924 specifically blocked SDF-1 binding to CXCR4 with IC 50 value of 0.079 nmol/L, and inhibited SDF-1-induced GTP binding with Kb value of 0.38 nmol/L. In human lymphoma U937 cells … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
130
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(132 citation statements)
references
References 35 publications
2
130
0
Order By: Relevance
“…[8][9][10][11][12][13][14][15][16] LY2510924 is a novel and potent selective peptide antagonist of CXCR4. 17 A recent phase 1 study in advanced cancers revealed good tolerability with mostly grade 1 to 2 adverse events, favorable pharmacokinetics, and target engagement as indicated by dose-dependent increases in CD34 1 cell mobilization. 18 Here, we report preclinical studies using LY2510924 to disrupt the SDF-1a/CXCR4 axis in AML cells in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16] LY2510924 is a novel and potent selective peptide antagonist of CXCR4. 17 A recent phase 1 study in advanced cancers revealed good tolerability with mostly grade 1 to 2 adverse events, favorable pharmacokinetics, and target engagement as indicated by dose-dependent increases in CD34 1 cell mobilization. 18 Here, we report preclinical studies using LY2510924 to disrupt the SDF-1a/CXCR4 axis in AML cells in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the protective role that this pathway plays, increased activity of this signaling axis is correlated with poor prognosis. 4,7,8,39,40 CXCR4 inhibitors currently being evaluated in the clinic, including small molecules, 23 peptides, 24,25 and an IgG4 Ab, [27][28][29][30] can mobilize tumor cells, sensitizing them to cell killing by chemotherapy. 17,41 PF-06747143, a novel humanized IgG1 Ab, binds to CXCR4 and potently inhibits CXCL12/CXCR4-mediated cell signaling pathways such as cAMP and cancer cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the ability of anti-CXCR4 agents to simply mobilize cells appears to be insufficient to drive antitumor activity. For instance, the CXCR4 peptide antagonists LY2510924 24 and BKT140/BL8040/TN14003 25 induce cell mobilization as monotherapies but failed to reduce tumor burden in clinical trials. 25,26 Interestingly, the CXCR4 partial agonist small molecule AMD3100 (Plerixafor; Mozobil), which induces mobilization of leukemic blasts from the BM, is undergoing clinical evaluation in hematologic malignancies in combination with chemotherapy, as a means to eliminate the mobilized cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike POL6326, the small molecule CXCR4 inhibitor TG-0054 (Burixafor) [29] and the cyclic peptide BKT-140 [30] have been tested with G-CSF and shown to synergistically augment HSC mobilization when given as a single dose after a standard course of G-CSF, results which were corroborated in human volunteers and patients with haematological malignancies [31][32][33][34]. Other promising CXCR4 antagonists in development for HSC mobilization include the cyclic peptide LY2510924 [35][36][37] and the small molecule ALT-1188 [38]. Notably, ALT-1188 has been shown to effectively mobilize murine HSPC when given as a single dose and synergistically when used in combination with G-CSF [38].…”
Section: Inhibitors Of the Cxcr4/sdf-1α Axismentioning
confidence: 99%